Pengembangan Media Pembelajaran Interaktif Berbasis Web Menggunakan Scratch Berdasarkan Representasi Matematika Siswa Kelas Empat - Alya Wahyu Kartika; Trimurtini (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to develop interactive learning media based on the Scratch website, designed according to the learning needs and mathematical representation abilities of fourth-grade elementary school students on the topic of fractions. Employing a Research and Development (R&D) framework using the ADDIE model, the study focused on the design, expert validation, and formative evaluation stages. The participants consisted of 51 students and 11 teachers from SDN Manyaran 02, Semarang, Central Java, involved in the limited implementation phase. The instruments used included a needs analysis questionnaire, content expert and media expert validation sheets, teacher and student response questionnaires, and documentation of student quiz results. The data were analyzed using both quantitative and qualitative approaches. The results showed that the developed media obtained a content expert validation score of 92.3% and a media expert validation score of 98%, both categorized as highly suitable. During the limited implementation phase, the teacher response rate reached 93%, while the student response rate reached 91.5%, both of which fell into the “highly suitable” category. Furthermore, the distribution of student quiz scores indicated positive learning outcomes, with an average score of 89.02. These findings suggest that the Scratch-based learning media aligns with students’ learning needs, is practical to implement, and has the potential to support the enhancement of mathematical representation abilities among elementary school students.